Implementasi Kebijakan Program Makan Bergizi Gratis Dalam Meningkatkan Kesejahteraan Masyarakat Miskin - Dea Amanda; Dinda Maharani; Eva Julia; Khoirun Nisa; Yulfidha Diah Riama; Khoiriya Ulfah (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The Free Nutritious Meal Program (MBG) is one of the Indonesian government's social policies aimed at improving public nutrition while reducing the economic burden of poor households. This study aims to analyze the implementation of the MBG policy in improving the welfare of poor communities. The method used in this article is qualitative descriptive with literature review and limited interview approaches. The study findings indicate that the MBG program contributes to reducing daily food expenses, increasing children's nutritional intake, and supporting educational participation among low-income families. However, several challenges remain, including unequal food distribution, menu quality control, and implementation supervision. The interview with a resident in Sukarame also showed that the program helped reduce household expenses and improved children's enthusiasm for attending school. This study concludes that the MBG program has positive potential in supporting social welfare if implemented consistently and transparently.